Grain receipts as collateral for agribusiness' financing - Garcia, Ivan (2006)
Jalisco's corn producers from the Cienega province are locked in a cycle of low profitability. The corn producers have been affected by the lack of access to adequate financial intermediaries such as banks. The cycle of low profitability contributes towards a low quality of life and a lack of competitiveness. Hence, farmers have not been able to adjust to the fierce competition from the US producers. A lack of trustworthy collateral is a major problem in order to get access to credits. The grain receipts system (GRS) provides a method of collateralizing crops for access to credits, using smart cards as a shortcut for cash withdrawals. With the GRS the risk is not intended to be eliminated; instead it is a mechanism where the risk is shared between the corn producers, elevators and banks which are the subject of analysis in this study using the agency theory.